Dynamically Deformable Protein Delivery Strategy Disassembles Neutrophil Extracellular Traps to Prevent Liver Metastasis. (29th July 2021) - Zhu, Lianghan; Li, Zhaoting; Liu, Ning; Sun, Honghao; Wang, Yixin; Sun, Minjie
Abstract: Neutrophil extracellular traps (NETs), consisting of chromatin DNA filaments coated with granule proteins, promote metastasis by enhancing tumor cell migration to distant organs. Recent studies indicate that NETs adhere to cancer cell membranes and enhance cell motility significantly to induce liver metastasis in patients with breast and colon cancers. Herein, a dynamically deformable protein delivery strategy is developed to prevent liver metastasis by disassembling NETs. Specifically, poly amino acid conjugating with polyethylene glycol (PAAP) is explored and synthesized for DNase‐1 delivery. Notably, PAAP/DNase‐1 degrades chromatin to induce apoptosis, followed by cell membrane rupture and remaining DNase‐1 releases to the extracellular. More importantly, the released DNase‐1 disassembles NET‐DNA to prevent liver metastasis induced by NET. In all, PAAP/DNase‐1 treatment not only suppresses tumor growth by degrading intracellular chromatin, but also prevents the liver metastasis by disassembling the NET‐NDA. This strategy may provide brand‐new inspiration to prevent the liver metastasis fundamentally in patients with metastatic colon and breast cancer. Abstract : Neutrophil extracellular traps (NETs) are capable of adhering to the cancer cell surface and promoting the migration and invasion of cells towards the liver, subsequently forming hepatic metastases. Thus, a dynamically deformable protein delivery strategy (PAAP/DNase‐1) is developed for liver metastasis prevention in patients with metastatic colon or breast cancer by disassembling NETs successfully.